Quality Control of the Traditional Patent Medicine Yimu Wan Based on SMRT Sequencing and DNA Barcoding - Jia, Jing; Xu, Zhichao; Xin, Tianyi; Shi, Linchun; Song, Jingyuan (Frontiers in Plant Science, 2017)
Substandard traditional patent medicines may lead to global safety-related issues. Protecting consumers from the health risks associated with the integrity and authenticity of herbal preparations is of great concern. Of particular concern is quality control for traditional patent medicines. Here, we establish an effective approach for verifying the biological composition of traditional patent medicines based on single-molecule real-time (SMRT) sequencing and DNA barcoding. Yimu Wan (YMW), a classical herbal prescription recorded in the Chinese Pharmacopoeia, was chosen to test the method. Two reference YMW samples were used to establish a standard method for analysis, which was then applied to three different batches of commercial YMW samples. A total of 3703 and 4810 circular-consensus sequencing (CCS) reads from two reference and three commercial YMW samples were mapped to the ITS2 and psbA-trnH regions, respectively. Moreover, comparison of intraspecific genetic distances based on SMRT sequencing data with reference data from Sanger sequencing revealed an ITS2 and psbA-trnH intergenic spacer that exhibited high intraspecific divergence, with the sites of variation showing significant differences within species. Using the CCS strategy for SMRT sequencing analysis was adequate to guarantee the accuracy of identification. This study demonstrates the application of SMRT sequencing to detect the biological ingredients of herbal preparations. SMRT sequencing provides an affordable way to monitor the legality and safety of traditional patent medicines.